Hrádok nad Váhom - Filip Ondrkál (Dissertationes Archaeologicae: Ex Instituto Archaeologico Universitatis de Rolando Eötvös Nominatae)
In the Bronze Age, the initial production of sheet metal vessels was limited to specialised workshops in eastern Mediterranean centres such as Troy or Mycenae, spreading slowly to the European hinterland. In this sense, the recently discovered hoard at Hrádok in Western Slovakia, dated to ca. 1225–1175 BC, represents the earliest and most complete set of bronzeworking tools in Central Europe, providing a deeper understanding of the making and decorating of bronze vessels in an Early Urnfield environment. Through a comprehensive evaluation of tin content analysis results of copper alloy vessels from western Eurasia, the spread of this most advanced contemporary technology could be reconstructed, highlighting the importance of such research in understanding the processes leading to the emergence of the Urnfield power structures and centralised political control over secondary metallurgy (the production of artefacts from already processed raw materials) in Europe in the Bronze Age.